Electrophysiological evidence for voltage-gated calcium channel 2 (Cav2) modulation of mechano- and thermosensitive spinal neuronal responses in a rat model of osteoarthritis. (1st October 2015) - Rahman, W.; Patel, R.; Dickenson, A.H.
Highlights: MIA-dependent antinociceptive effect of TROX-1 on neuronal activity. Alterations in Cav 2.2 channel function contribute to osteoarthritic (OA) pain. Blocking Cav 2.2 channels has therapeutic potential for treating OA pain. Abstract: Osteoarthritis (OA) remains one of the greatest healthcare burdens in western society, with chronic debilitating pain-dominating clinical presentation yet therapeutic strategies are inadequate in many patients. Development of better analgesics is contingent on improved understanding of the molecular mechanisms mediating OA pain. Voltage-gated calcium channels 2.2 (Cav 2.2) play a critical role in spinal nociceptive transmission, therefore blocking Cav 2.2 activity represents an attractive opportunity for OA pain treatment, but the only available licensed Cav 2.2 antagonist ziconitide (PrilatTM) is of limited use. TROX-1 is an orally available, use dependent and state-selective Cav 2 antagonist, exerting its analgesic effect primarily via Cav 2.2 blockade, with an improved therapeutic window compared with ziconitide. Using a rat model of monosodium iodoacetate (MIA), 2 mg, induced OA we used in vivo electrophysiology to assess the effects of spinal or systemic administration of TROX-1 on the evoked activity of wide dynamic range spinal dorsal horn neurons in response to electrical, natural mechanical (dynamic brush and von Frey 2, 8, 26 and 6 g) and thermal (40, 45 and 45 °C) stimuli applied to the peripheral receptive field. MIA injection into the knee joint resulted in mechanical hypersensitivity of the ipsilateral hind paw and weight-bearing asymmetry. Spinal administration of TROX-1 (0.1 and 1 μg/50 μl) produced a significant dose-related inhibition of dynamic brush, mechanical (von Frey filament (vF) 8, 26 and 60 g) and noxious thermal-(45 and 48 °C) evoked neuronal responses in MIA rats only. Systemic administration of TROX-1 produced a significant inhibition of the mechanical-(vF 8, 26 and 60 g) evoked neuronal responses in MIA rats. TROX-1 did not produce any significant effect on any neuronal measure in Sham controls. Our in vivo electrophysiological results demonstrate a pathological state-dependent effect of TROX-1, which suggests an increased functional role of Cav 2, likely Cav 2.2, channels in mediating OA pain.